The Study on 3D Simulation Usage in Teaching and Learning Process - Rahim, S. S.; Sazli, N. S. W.; Alias, S. S.; Mat Rani, M. I. (2011)
Abstract – Simulation can be a powerful tool if understood and used properly. Simulation can be an extremely useful instructional aid. This paper will present the study on 3D simulation usage in teaching and learning process. The paper will focus on two projects developed in 3D simulation domain which are Photosynthesis 3D Simulation (Light Dependent Reaction) and also 3D Simulation of 2-Stroke and 4-Stroke Engine. The simulation can help in introducing components that are purely virtual, concepts that cannot be easily realized, but still useful for learning. There are some difficulties to the students where they have to face during learning process, especially the nature process that hard to see with naked eyes. Various means used by teachers to deliver lessons to students but how effective the teaching method used is depends on the lecturer or teacher. Textbooks, references book, slide presentation and fact in graphics are some of the current teaching methods that are still used. This method is not entirely effective, but for students who have a weak imagination is pathetic. Therefore, 3D simulation is developed to overcome this difficulty.